Aquatic animal resources in Prehistoric Aegean, Greece - Mylona, Dimitra (J Biol Res (Thessalon), 2014)
This paper explores the early stages in the history of fishing in the Aegean Sea in Greece, and highlights its formative phases and its specific characteristics in different points in time. This is testified by various physical remains, such as fish bones, fishing tools, and representations in art, which are gathered in the course of archaeological research. The aquatic resources in the Aegean Sea have been exploited and managed for millennia by communities that lived near the water and often made a living from it. The earliest evidence for a systematic, intensive exploitation of marine resources in the Aegean Sea dates to the Mesolithic, eleven millennia ago. In the Neolithic period, the adoption of a sedentary, agro-pastoral way of life led to a reduction in the intensity of fishing and shellfish gathering. Its importance as an economic resource remained high only in certain regions of rich, eutrophic waters. In the Bronze Age, an era of social complexity and centralized economy, the exploitation of aquatic, mostly marine, resources became a complex, multi-faceted activity which involved subsistence, industry and ideology. The range of preferred fish and invertebrate species, the fishing technology, and the processing of fish and shellfish in order to produce elaborate foods or prestige items are all traceable aspects of the complex relationship between humans and the aquatic resources throughout the prehistory of fishing and shellfish gathering in the Aegean area. The broadening of collaboration between archaeology and physical sciences offers new means to explore these issues in a more thorough and nuanced manner.